The influence of weight gain patterns in pregnancy on fetal growth using cluster analysis in an obese and nonobese population. (29th May 2013) - Galjaard, S.; Pexsters, A.; Devlieger, R.; Guelinckx, I.; Abdallah, Y.; Lewis, C.; van, B.; Bourne, T.; Timmerman, D.; Luts, J.
<x xml:space="preserve">Abstract</x> Objective Excessive weight gain during pregnancy has an important influence on fetal growth and on weight development in future generations. Design and Methods A prospective cohort study of 325 obese and nonobese Caucasian women with naturally conceived, singleton pregnancies was performed. They were followed up until delivery for maternal weight gain and for fetal growth with ultrasound‐based weight estimations and final birth weight. Using cluster analysis distinct profiles of maternal weight gain during pregnancy were obtained. Longitudinal regression analysis was performed to investigate the relationship of the maternal weight gain profile and BMI on fetal growth and final birth weight. Results Cluster analysis revealed four discernable maternal weight gain profiles: 12 cases (3.7%) ended up at their starting weight or decreased in weight (cluster 1), 16 cases (4.9%) who slightly increased in weight (maximum 4 kg) as compared to their initial weight (cluster 2), 114 cases (35.1%) who gained between 4 and 12 kg in weight (cluster 3), and 183 cases (56.3%) who showed the largest weight gain: more than 12 kg (cluster 4). There were statistically significant differences in fetal growth associated with weight gain cluster, which became apparent late in the second trimester and increased toward the end of pregnancy. Maternal BMI and maternal weight gain profile were independent predictors of fetal growth and birth weight. Conclusions Therefore, the conclusion is that the cluster analysis permits to discern four gestational weight gain (GWG) patterns in obese and nonobese subjects and that both maternal BMI and maternal weight gain pattern during pregnancy positively influence fetal growth and birth weight.